2013
DOI: 10.1128/aac.01735-12
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of 8-Hydroxyserrulat-14-en-19-oic Acid for Treatment of Implant-Associated Infections

Abstract: Treatment options are limited for implant-associated infections (IAI) that are mainly caused by biofilm-forming staphylococci. We report here on the activity of the serrulatane compound 8-hydroxyserrulat-14-en-19-oic acid (EN4), a diterpene isolated from the Australian plant Eremophila neglecta. EN4 elicited antimicrobial activity toward various Gram-positive bacteria but not to Gram-negative bacteria. It showed a similar bactericidal effect against logarithmic-phase, stationary-phase, and adherent Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 47 publications
(45 reference statements)
5
21
0
Order By: Relevance
“…The strains were stored at Ϫ80°C with the cryovial bead preservation system (Microbank; Pro-Lab Diagnostics, Richmond Hill, Ontario, Canada). The inoculum for in vivo and in vitro studies was prepared as previously published (8,30). Bacterial numbers were determined by plating aliquots from appropriate dilutions on MHA, followed by colony counting after 24 h of incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains were stored at Ϫ80°C with the cryovial bead preservation system (Microbank; Pro-Lab Diagnostics, Richmond Hill, Ontario, Canada). The inoculum for in vivo and in vitro studies was prepared as previously published (8,30). Bacterial numbers were determined by plating aliquots from appropriate dilutions on MHA, followed by colony counting after 24 h of incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their ability to rapidly form biofilm on the inert surface, they manage to grow and evade not only the defensive mechanisms of the host but also the bactericidal activity of antibiotics (7). Effective treatment of IAIs therefore involves surgery, often resulting in the removal of the nonsalvageable biomaterial followed by a long course of antibiotic therapy (8,9).…”
mentioning
confidence: 99%
“…The concentration of bactericidal dose is only three to six folds higher than the bactericidal dose [ 120 ]. 8-hydroxyserrulat-14-en-19-oic acid, a plant-derived serrulatane diterpenoid (extracted from the Australian medicinal plant Eremophila neglecta ) showed anti-biofilm formation activity against Gram-positive bacterial but not Gram-negative bacteria by inhibiting the macromolecular biosynthesis of the bacterial membrane [ 121 ]. Table 6 summarises examples of diterpenoids with anti-biofilm activities…”
Section: Promising Novel Therapies For Prevention and Treatment Ofmentioning
confidence: 99%
“…The MID is an indicator of staphylococcal virulence in this model. For S. aureus it ranges between approximately 5 × 10 2 –5 × 10 3 CFU/cage [ 9 , 30 , 86 ]. In contrast, the MID of S. epidermidis is much higher, namely above 10 6 CFU/cage, and spontaneous clearing occurs, if bacteria are not injected during the perioperative period [ 83 ].…”
Section: Tissue Cage Infection Modelmentioning
confidence: 99%
“…In vivo however neither bactericidal nor cytotoxic effects were present, indicating an inhibition of its activity. Inhibition assays revealed that this was caused by interaction of EN4 with albumin [ 86 ].…”
Section: Tissue Cage Infection Modelmentioning
confidence: 99%